2021
DOI: 10.1038/s41598-021-91439-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and comparative study on the structural and optical properties of ZnO doped with Ni and Ag nanopowders fabricated by sol gel technique

Abstract: In this work we have tried to prepare Ni and Ag doped ZnO nanopowders using the sol gel technique. The influence of Ni and Ag (1, 3 and 5 mol.%) on the crystalline structure and optical properties of ZnO was investigated. The samples were characterized by XRD, FTIR and UV–visible spectrophotometer. XRD patterns confirmed the wurtzite formation of doped and undoped ZnO nanopowders. The average crystallite sizes of the prepared samples found from XRD were 19 nm for undoped ZnO, from 17 to 22 nm for Ni-ZnO and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 39 publications
4
40
0
Order By: Relevance
“…54 Typically, the characteristic peaks at 31.8, 34.5, 36.3, 47.6, 56.7, 63.0, 68.0, and 69.3 belong to the Miller indices of (1 0 0), (0 0 2), (1 0 1), (1 0 2), (1 1 0), (1 0 3), (1 1 2), and (2 0 1) planes, respectively. 55 The XRD pattern of MCC displays the characteristic peaks of cellulose at 15.3, 16.4, 22.6, and 34.8 2θ which are in accordance with the crystallographic planes of (1 À1 0), (1 1 0), (2 0 0) and (0 0 4) of the cellulose I structure, respectively. [56][57][58][59][60] As expected, the XRD pattern of M-ZnO shows the combined characteristic peaks of both A-ZnO and MCC indicating the existence of ZnO in the M-ZnO sample.…”
Section: Characterization Of Znos and MCCsupporting
confidence: 52%
See 1 more Smart Citation
“…54 Typically, the characteristic peaks at 31.8, 34.5, 36.3, 47.6, 56.7, 63.0, 68.0, and 69.3 belong to the Miller indices of (1 0 0), (0 0 2), (1 0 1), (1 0 2), (1 1 0), (1 0 3), (1 1 2), and (2 0 1) planes, respectively. 55 The XRD pattern of MCC displays the characteristic peaks of cellulose at 15.3, 16.4, 22.6, and 34.8 2θ which are in accordance with the crystallographic planes of (1 À1 0), (1 1 0), (2 0 0) and (0 0 4) of the cellulose I structure, respectively. [56][57][58][59][60] As expected, the XRD pattern of M-ZnO shows the combined characteristic peaks of both A-ZnO and MCC indicating the existence of ZnO in the M-ZnO sample.…”
Section: Characterization Of Znos and MCCsupporting
confidence: 52%
“…36‐1451, indicating the hexagonal wurtzite structure of A‐ZnO 54 . Typically, the characteristic peaks at 31.8, 34.5, 36.3, 47.6, 56.7, 63.0, 68.0, and 69.3° belong to the Miller indices of (1 0 0), (0 0 2), (1 0 1), (1 0 2), (1 1 0), (1 0 3), (1 1 2), and (2 0 1) planes, respectively 55 . The XRD pattern of MCC displays the characteristic peaks of cellulose at 15.3, 16.4, 22.6, and 34.8° 2 θ which are in accordance with the crystallographic planes of (1 −1 0), (1 1 0), (2 0 0) and (0 0 4) of the cellulose I structure, respectively 56–60 .…”
Section: Resultsmentioning
confidence: 99%
“…[38] The intensity of (111), and (200) peaks confirmed the formation of Ag in ZnO crystal ChemistrySelect lattice (JCPSD card no 04-0783). [39] Figure S2 illustrates the XRD pattern from 30°to 37.2°. It is clearly shown that the Zn peaks which are corresponding to Miller indices (100), (002), and (101), are slightly shifted to a higher angle side with increasing Ag doping concentration from 0 % to 20 %.…”
Section: Structural Analysismentioning
confidence: 99%
“…As seen, c/a ratio of all samples (table 2) is smaller than ideal which might be linked to the presence of oxygen vacancies V O and extended defects [30]. The average crystallite sizes of the films were estimated using Debye Scherrer's formula, also the microstrain and dislocation density was computed by below equations [31][32][33];…”
Section: Structural Characterizationmentioning
confidence: 99%